Serum Immunoglobulin G Is Associated With Decreased Risk of Pancreatic Cancer in the Swedish AMORIS Study - Sollie, Sam; Santaolalla, Aida; Michaud, Dominique S.; Sarker, Debashis; Karagiannis, Sophia N.; Josephs, Debra H.; Hammar, Niklas; Walldius, Goran; Garmo, Hans; Holmberg, Lars; Jungner, Ingmar; Van Hemelrijck, Mieke (Frontiers in Oncology, 2020)
Background: Emerging evidence points to potential roles of the humoral immune responses in the development of pancreatic cancer. We evaluated associations between pre-diagnostic serum markers of the humoral immune system (immunoglobulin A (IgA), immunoglobulin G (IgG) and immunoglobulin M (IgM)), and pancreatic cancer risk in the Swedish Apolipoprotein-related MORtality RISk (AMORIS) study. Methods: We selected all participants (≥20 years old) with baseline measurements of IgA, IgG or IgM (n= 41900, 136221, and 29919, respectively). Participants were excluded if they had a history of chronic pancreatitis and individuals were free from pancreatic cancer at baseline. Multivariate Cox proportional hazards regression was used to estimate risk of pancreatic cancer for medical cut-offs of IgA, IgG and IgM. Results: Compared to the reference level of 6.10-14.99 g/L, risk of pancreatic cancer was elevated among those with IgG levels <6.10 g/L [HR: 1.69 (95% CI 0.99-2.87)], and an inverse association was observed among those with IgG levels ≥15.00 g/L [0.82 (95% CI 0.64-1.05); Ptrend = 0.027]. The association appeared to be stronger for women than men [HR: 0.64 (95% CI 0.43-0.97) and 0.95 (95% CI 0.69-1.29) respectively]. No associations were observed with IgA or IgM. Conclusion: An inverse association was observed between pre-diagnostic serum levels of IgG and risk of pancreatic cancer. Our findings highlight the need to further investigate the role of immune response in pancreatic cancer aetiology.